(824) Classified Index to Articles of the Periodicals for the Years 1965 and 1966 فهرس مصنف لمقالات الدوريات لعامى 1965 و 1966 - Ewieda, Mohammed (The Institute of National Planning, 2025)
Since its establishment, the Documentation Center has recognized the importance of bibliographical services as an integral part of economic and planning research, serving as an essential tool for its progress and development. It is normal that the daily preoccupations of researchers hinder regular follow-up of new studies without adequate support from the Documentation Center in their fields. Researchers want to know what others have done to avoid wasted efforts. The Documentation Center of the National Institute of Planning has prepared this index to scientific journals and periodicals received in 1965 and 1966. It is hoped that this document will be a useful aid to scholars and researchers both within and outside the institute.